Polymer-encapsulated organic nanocrystals for single photon emission - Schofield,RC; Bogusz,DP; Hoggarth,RA; Nur,S; Major,KD; Clark,AS (Optical Materials Express, 2020)
We demonstrate an emulsion-polymerisation technique to embed dibenzoterrylene-doped anthracene nanocrystals in polymethyl methacrylate (PMMA) nanocapsules. The nanocapsules require no further protection after fabrication and are resistant to sublimation compared to unprotected anthracene. The room temperature emission from single dibenzoterrylene molecules is stable and when cooled to cryogenic temperatures we see no change in their excellent optical properties compared to existing growth methods. We also show emission from nanocapsules embedded in a thin layer of titanium dioxide, highlighting their potential for integration into hybrid nanophotonic devices.